Фортификация Чугуевского городища - Свистун, Г.Е. (Степи Европы в эпоху средневековья, 2012)
За всю историю археологических исследований салтовских древностей памятникам, расположенным в черте современных городов, уделялось незаслуженно малое внимание. Это связано, прежде всего, с объективно возникающими трудностями урбанистической археологии: ограниченностью доступных для исследования площадей, во многих случаях значительныминарушениями культурного слоя и его залеганием под мощными отложениями современной хозяйственной деятельности, препятствиями со стороны коммунальных служб и собственников земельных участков. In the early Middle Ages fortifications of the Chuguiev hillfort the traditional designs characteristic of the building skills of the Saltov population combined with the construction methods developed during their residence in the Severskiy Donets valley were used. A synthesis of traditional methods and innovative approaches while fortifying the Chuguiev fortress was prompted by the nature of available building materials and the goals of their defence strategy which was to be anticipated during the expected enemy’s warfare. Defensive structures were made of stone and brick and looked like an unpaved rampart with stone blocks on its slopes and a brick parapet on top. Defence of the Chuguiev hillfort was organized by the fosse-rampart and escarp-rampart principle.